The Southern Strategy Revisited : Republican Top-Down Advancement in the South - Aistrup, Joseph A., 1960- (Book collections on Project MUSE., 1996)
The 1994 elections represented a watershed year for southern Republicans. For the first time since Reconstruction, they gained control of a majority of national seats and governorships. Yet, despite these impressive gains, southern Republicans control only three of twenty-two state legislative chambers and 37 percent of state legislative seats. Joseph A. Aistrup addresses why this divergence between the national and subnational levels persists even after GOP national landslides in 1972, 1980, 1984, 1988, and 1994. Explanations for this divergence lie in the interaction between the Republicans'